Tools and Techniques of Leadership and Management : Meeting the Challenge of Complexity - Stacey, Ralph (Taylor and Francis, 2012)
Many of today’s books on the tools and techniques of leadership and management provide descriptions of long lists for use in decision-making, leading, coaching and project management. This book takes a completely different approach. It contests the claims that the tools and techniques are based on evidence and explains why human activities of leading and managing are simply not amenable to scientific proof and consequently, why long-term futures of organizations are unpredictable.